Understanding piezocatalysis, pyrocatalysis and ferrocatalysis - Domingo, Neus (Frontiers in Nanotechnology, 2024)
The last decade has witnessed the emergence of the application of piezoelectric and ferroelectric materials for catalytic and photocatalytic applications that harness light, thermal and mechanical energy into chemical reactions. This article surveys the different concepts of pyro-and piezocatalysis and differences with respect to ferrocatalysis and switchable catalysis and delves into the current understanding of the mechanisms underlying piezocatalysis. The outlook for advancing in the surface science studies required for the design of new and better catalysts based on polar electromechanically active materials is discussed in the context of the state of the art experimental studies and potential future nanoscience developments.